Comparison of shear bond strength and color reproduction of two different high-performance polymers veneered with two different thicknesses of resin composite: an in-vitro study - Ahmed, Gehad Abdelgawad; El-Etreby, Amr; El-Fattah, Ghada ABD (Brazilian Dental Science, 2023)
Objective: to evaluate the effect of material type and veneer thickness on the final color and shear bond strength of PEEK bilayered restorations. Material and Methods: sixty-four square-shaped core specimens (7×7×2), were fabricated by CAD/CAM technology from two high-strength polymers, BioHPP (High-Performance Polymer, group B n=32), and Pekkton® ivory (PolyEtherKetoneKetone, group P n=32) then were veneered with resin composite (crea.lign dentin A3). Specimens from each group were divided (n=16) according to the veneer layer thickness (0.5 & 1 mm), then according to the test applied (n=8), either deltaE or shear bond strength (SBS). Specimen surfaces were treated according to the manufacturer’s instructions. Specimens were veneered according to the manufacturer’s instructions.The mode of failure was evaluated under a stereomicroscope at 40 x magnification after the shear bond strength test. Results: data showed parametric distribution and variance homogeneity and were analyzed using two-way ANOVA. The significance level was set at p0.05). Conclusion: the thickness of the resin composite veneer can significantly affect the final esthetic outcome and shear bond strength of a bilayered restoration.KEYWORDSComposite resins; Polymers; Polyetheretherketone; Polyetherketoneketone; Shear strength.